Immunization practices in children with a history of allergies - (:unkn) unknown (TURKISH PEDIATRICS ASSOC, 2020)
Aim: In the presence of food allergies, especially egg allergies, primary physicians in Turkey avoid vaccine administration and refer children to a hospital setting. We aimed to evaluate children who had allergies or suspected allergies and were referred to our Well Child Clinic in a university hospital for vaccination. Material and Methods: Charts of all children referred to our clinic due to concerns for allergies in the last two years, were reviewed. Demographic data, laboratory evaluation and reactions after immunization were recorded. Results: A total of 122 children with or without a confirmed diagnosis of allergies were referred by primary physicians. In the history, 50 children (43.5%) had reactions with egg, 42 (36.5%) had reactions with multiple foods, nine (7.8%) had reactions with milk and seven (6.1%) had reactions with a previous vaccination. The most common reaction was rash (n=89, 86.4%). Nine children reported anaphylaxis. Skin testing or serum allergen specific IgE measurement revealed that 66 (54.1%) children had sensitization to egg white and 25 (20.5%) had sensitization to egg yolk. Most children (n=87, 71.9%) were referred for all the 12th-month vaccines, and 21 children were referred only for the measles-mumps-rubella vaccine (n=21, 17.4%). The median delay time in the administration of the measles-mumps-rubella vaccine was 20.0 (interquartile range: 8.7-41.2) days. No reaction was observed except for one child reporting a slight rash several hours after vaccination. Conclusion: Egg allergy was the most common barrier of vaccine administration in children referred from family physicians. Given the absence of any reactions, we support the administration of the measles-mumps-rubella vaccine in primary care settings to prevent delays in national vaccine schedule.
Keywords: Allergy; children; egg; immunization; measles-mumps-rubella; IMMEDIATE-TYPE REACTIONS; ADVERSE-REACTIONS; MEASLES; VACCINE; MUMPS; ANAPHYLAXIS; RUBELLA; GUIDELINES; GELATIN; IGE